The Behavior of Street Children within a Cultural Context: A Study on the Communication Life of Street Children within a Typical Indonesian Society - Yusuf Yusuf (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
In Indonesia, unfortunate children facing dire circumstances, including victims of war, forced labor, child abuse, and human trafficking, are prevalent. Among them, street kids endure rapid growth due to various factors, living in abusive environments and spending approximately eight hours daily wandering the streets. This study aimed to explore the uniqueness of street children near the tombs of Islamic saints (Wali), where they descend to interact with pilgrims during religious events, seeking alms. Employing a phenomenological approach. Data Collection was by interview, field observation together with ethnographic techniques on street children’s motivations for begging and their communication behaviors in capturing pilgrims’ attention. Findings revealed that economic reasons and peer influence were primary motives for the children’s street presence. Additionally, sacred events like Muludan, Malam Pelal, Syawalan, Serenan, Sedekah Bumi/Nadran, and Kliwonan marked peak times for their begging activities, associated with poverty and ritualistic behaviors. Understanding street children’s communication behaviors and dynamics in this cultural context offers valuable insights for social interventions and support.